Hubungan Antara Waktu Tunggu Terhadap Kepuasan Pasien Di Instalasi Rawat Jalan Rumah Sakit - Chisiliya Tri Hasinta; Desak Putu Kristian Purnamiasih; Monica Kartini (Jurnal Kesehatan, 2025)
Patient satisfaction is a measure of the feelings that arise in response to the health care received, compared with expectations. One of the determining factors of patient satisfaction is the service waiting time. Waiting time is the length of time from when a patient registers until they are seen by a doctor. Outpatient services are one indicator of service quality that shapes a hospital's initial image. This study aims to determine the correlation between waiting time and patient satisfaction in the outpatient department of Ngesti Waluyo Hospital. This study used a quantitative, cross-sectional design. A sample of 100 respondents was selected using a purposive sampling technique. Data were collected through observation and validated, reliable questionnaires. Data was then analysed using the Spearman Rho test. The results showed a significant relationship between waiting time and patient satisfaction (p-value=0.012; r=0.250), indicating a weak relationship. This means that the longer the wait, the lower the patient satisfaction. This research suggests that hospital management should evaluate and improve service flow and implement a digital queuing system.